2012
DOI: 10.1002/cvde.201106953
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Boron Doping Level on The Morphology and Structure of Ultra/Nanocrystalline Diamond Films

Abstract: In this work, boron-doped nanocrystalline diamond (BDND) films are grown on silicon substrates by hot-filament (HF)CVD in Ar/H 2 /CH 4 gas mixtures. In this study, the transition from ultra-nanocrystalline to nanocrystalline diamond films is clearly shown by the addition of boron dopant to the growth of the gas mixture. The doping process consists of an additional H 2 line passing through a bubbler containing B 2 O 3 dissolved in methanol with various B/C ratios. Five sample sets are obtained with doping in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The peaks observed at 1135 and 1475 cm –1 for undoped NCD and peaks 1150 and 1477 cm –1 for B-NCD (i.e., peaks i and iii in both cases) correspond to the C–H vibration modes, which also have been reported previously in these kind of films . The broad hump around 1550 cm –1 for undoped NCD (peak iv), 1600 cm –1 for B-NCD (peak iv) and 1550 cm –1 for P-NCD (peak i) are attributed to sp 2 -bonded carbon, which is predominantly expected to be present at the grain boundaries. , Finally, the peak observed at 1220 cm –1 for B-NCD film (peak v) can be ascribed to boron doping. , …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The peaks observed at 1135 and 1475 cm –1 for undoped NCD and peaks 1150 and 1477 cm –1 for B-NCD (i.e., peaks i and iii in both cases) correspond to the C–H vibration modes, which also have been reported previously in these kind of films . The broad hump around 1550 cm –1 for undoped NCD (peak iv), 1600 cm –1 for B-NCD (peak iv) and 1550 cm –1 for P-NCD (peak i) are attributed to sp 2 -bonded carbon, which is predominantly expected to be present at the grain boundaries. , Finally, the peak observed at 1220 cm –1 for B-NCD film (peak v) can be ascribed to boron doping. , …”
Section: Resultssupporting
confidence: 84%
“…30,31 Finally, the peak observed at 1220 cm −1 for B-NCD film (peak v) can be ascribed to boron doping. 32,33 To further characterize the surface of NCD films, we carried out XPS valence band measurements. Figure 4 are linked to H 1s orbitals, (ii) a peak around ∼12 eV that corresponds to the valence band derived from the 2s−2p hybridized levels of the diamond, (iii) a peak around ∼17 eV related to the 2s level of the diamond and (iv) a low-intensity peak around ∼25 eV, which is ascribed to the photoemission from O 2s.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the conclusions obtained with the Raman spectra analysis. The difference in the films thickness may be related to the growth rate, which tends to decrease as the doping level increases, as also observed by Souza et al [22]. This occurs because boron affects the nucleus formation during the first step of growth.…”
supporting
confidence: 54%
“…Oxygen is known to lead to potential chemical reactions with species in the gas phase and to the consumption of some carbon and boron species, which usually reduces the diamond growth rate. Besides, as the oxygen concentration increases, the growth rate decreases because defective sites can be formed on graphitic carbon layers, which are potential nucleation sites [22]. Issaoui et al [23] have also reported that the addition of a small amount of oxygen (0.25%) with boron can drastically change the growth rates in the different crystallographic directions.…”
mentioning
confidence: 99%
“…The conductivity of diamond is obtained via incorporation of nitrogen into the grain boundaries (N-UNCD) or substitutional doping with boron, that sits into the diamond crystal lattice (B-UNCD) [5], [6]. It has been reported by Sumant et al [7] that the work of adhesion between two undoped UNCD surfaces is (59.2 ± 2.0) mJ/m 2 and decreases to (10.2 ± 0.4) mJ/m 2 , if the diamond is previously treated with hydrogen plasma.…”
Section: Introductionmentioning
confidence: 99%